Lawyers as money laundering enablers? An evolving and contentious relationship - Levi, Michael (Global crime, 2022)
Using limited datasets and case studies drawn from the Global North and South, this article critically considers the available evidence about the involvement of lawyers in elite money laundering and attempts to control their involvement. In addition to lawyers’ lobbying and drafting laws , the normal focus of the ‘enablers’ discourse is on lawyers using expert knowledge and legal professional privilege/professional secrecy to facilitate frauds and to conceal the criminal origins of the funds of others. In few known laundering-for-others casesis there much evidence that lawyer assistance goes beyond doing their normal business: setting up constructions for clients that avoid external scrutiny is usually legal. It is implausible to fully resolve the extent to which lawyer ‘enablers’ are, respectively, naïve, negligent, wilfully blind and/or intentionally criminal. Within-firm supervision and both real and expected regulatory/criminal justice/reputational controls may have an impact, but the evidence base for assessing control effectiveness remains weak.